Solid State Characterization and Dissolution Enhancement of Nevirapine Cocrystals - Prabhakar Panzade; Giridhar Shendarkar; Deepak Kulkarni; Santosh Shelke (Tabriz University of Medical Sciences, 2021)
Purpose: Novel cocrystals of nevirapine (NP) were designed and prepared with salicylamide and 3-hydroxy benzoic acid (3-HBA). Methods: The cocrystals were prepared by solvent drop grinding method by adding few drops of acetone to enhance the solubility and dissolution. The drug and cocrystals were characterized by differential scanning calorimetry (DSC) and powder x-ray diffraction (PXRD). The solubility of NP, its wet ground form, and cocrystals were investigated at different pH. Moreover, the effect of surfactant on solubility of cocrystals was also studied. Finally, intrinsic dissolution rate (IDR) and stability of cocrystals was examined. Results: The characterization of cocrystals by DSC and PXRD revealed formation of new solid forms due to changes in thermogram and PXRD pattern. The cocrystal of NP with 3-HBA showed 4.5 folds greater solubility in pH 1.2 buffer and 5.5 folds in 1% Tween 80 as compared to original drug. IDR of cocrystals was higher than the pure drug in 0.1 N hydrochloric acid (HCl). Moreover, cocrystals were found physically stable after 3 months as evident from unchanged IDR. Conclusion: Hence, the present research indicates the new stable solid forms of NP with improved dissolution rate than pure drug.